The influence of resistance to change antecedents, dialogic communication and attitude towards change on education transformation programme / Ahmad Syahmi Ahmad Fadzil - Ahmad Fadzil, Ahmad Syahmi (2020)
The current evolving landscape of education calls for a better change management. Nonetheless, the lack of valid and effective framework for managing change particularly in managing education transformation programme is a growing concern. The change failure rate still persists dominantly as any change event will likely to fail rather than to triumph. Among the key contributors to change failures are resistance to change and communication fiasco. Change resistance can manifest through many forms and additionally, there are numerous methods of communication that can influence individual attitude on organizational change. Consequently, there is an urgent need for better understanding these crucial variables of change. This research thus proposed a new conceptual framework in organizational change study by validated the antecedents of change resistance through taxonomical perspectives and have tested the mediation effect of dialogic communication between the resistance taxonomies and attitude towards change. The population of this study is narrowed-down to the primary and secondary public-school teachers residing in Selangor. Pre-test and pilot test were conducted to establish face validity and construct measurement validation. Data collection was then made via 400 self-distributed questionnaires in the parent study through multistage sampling technique. A total of 333 usable questionnaires were subsequently analyzed by using the current PLS-SEM technique and reporting procedures. The result showed that all the antecedents of change resistance were positively significant according to their respective taxonomies and dialogic communication was found to mediates change programme resistance taxonomy. The results suggested that the framework used in this study may provide a wider view of managing resistance to change and have provided additional insight of how dialogic communication can mediate change. This study is optimistic that the findings can contribute to the improvement of managing change, particularly on the education transformation programme.